The gravity load simulator – Re-visited. (August 2020) - Wang, P.; Turvey, G.J.
Abstract: A review of loading arrangements for lateral buckling tests on pultruded glass fibre reinforced polymer (GFRP) beams is presented. It is suggested that the Gravity Load Simulator (GLS), used for similar tests on steel beams could also be used for lateral buckling tests on GFRP beams and, moreover, it could be analysed and designed using exact calculations rather than the iterative method used more than 50 years ago. This conclusion is demonstrated by re-analysing the old iteratively designed GLS. The exact analysis is then used to analyse and design a new GLS for lateral buckling tests on pultruded GFRP beams. The new GLS was fabricated from aluminium bar and plate and details of its overall dimensions and layout and the types of bearings used in its pin joints are described. Thereafter, the test arrangement and instrumentation used to demonstrate the GLS's accuracy, i.e. maintaining the horizontal translation of the jack's base as the GLS sways in the lateral buckling plane, is presented. It is shown that the GLS performs extremely well and its use in laboratory testing is illustrated.